A Study On The Effect Of Process Parameters On Weld Width And Heat Affected Zone Of Pulsed Laser Welding Of Dissimilar Transparent Thermoplastics Without Filler Materials In Lap Joint Configuration. (2018) - Bhattacharya, Raktim; Kumar, Nitesh; Kumar, Nikhil; Bandyopadhyay, Asish
Abstract: In the present work, through transmission laser welding of polycarbonate and acrylic have been conducted forming lap joint configuration. The effect of process parameters, namely, laser power, scanning speed and frequency on the weld width and HAZ (Heat affected zone) of weld bead geometry have been investigated, by using an empirical model developed by response surface methodology (RSM). The quadratic model has been developed to correlate the input parameters with responses. Also analysis-of-variance (ANOVA) has been conducted to find out the significant parameter/s in the process. It is found that power and scanning speed have significant influence in controlling the weld width. Whereas, power, frequency and scanning speed have played that role in case of HAZ. The statistical software design expert 10 has been used for experimental design and analysis.